PENGARUH WORKING CAPITAL TO TOTAL ASSETS, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PT BUKIT ASAM (PERSERO) TBK PERIODE 2009-2014 - Lina Sari; Bambang Purwanto (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
Working Capital To Total Assets (WCTA), debt to equity ratio (DER), total asset turnover(TAT), and net profit margin (NPM) describes the level of the company's ability to meet its short-longfunds which will boost profit growth. The higher WCTA, TAT and NPM shows the level of sales andthe more efficient use of assets. DER which is lower will boost corporate profits. This shows theefficiency and increased sales that will raise earnings in PT Bukit Asam (Persero) Tbk.The results of calculations by t test (partial regression test) showed that WCTA has nosignificant effect on earnings growth. DER has no significant effect on earnings growth. TAT hassignificant effect on earnings growth. NPM has no significant effect on earnings growth. The resultsof calculations by F test (simultaneous regression test) showed that WCTA, DER, NPM and TATcollectivelyhave no significant effect on earnings growth at PT Bukit Asam (Persero)